(untitled) (Bangladesh Journal of Pharmacology, 2014)
Rumex dentatus is well known plant of Polygonaceae family which is widely used in traditional medicine to treat gastrointestinal tract. R. dentatus at doses 250 and 500 mg/kg significance decreased (p<0.001) the elevated level of ALT, AST, ALP and bilirubin induced by paracetamol and results are comparable (p<0.001) with silymarin. The results were supported by histopathological investigations, phytochemical screening and detection of hepatoprotective active constituents e.g quercetin, kaempferol, myricetin by HPLC. So, it is concluded that R. dentatus has hepatoprotective effect against paracetamol liver damage in mice.